A pilot study examining the speed and accuracy of triage for simulated disaster patients in an emergency department setting: Comparison of a computerized version of Canadian Triage Acuity Scale (CTAS) and Simple Triage and Rapid Treatment (START) methods. Issue 5 (28th October 2016) - Curran-Sills, Gwynn; Franc, Jeffrey M.
ABSTRACT: Objective: To compare emergency department triage nurses' time to triage and accuracy of a simulated mass casualty incident (MCI) population using a computerized version of CTAS or START systems. Methods: This pilot study was a prospective trial using a convenience sample. A total of 20 ED triage nurses, 10 in each arm of the study, were recruited. The paper-based questionnaire contained nine simulated MCI vignettes. An expert panel arrived at consensuses on the wording of the vignettes and created a standard triage score from which to compare the study participants. Linear regression and chi-squared test were used to examine the time to triage and accuracy of triage, respectively. Results: The mean triage time for computerized CTAS (cCTAS) and START were 138 seconds/patient and 33 seconds/patient, respectively. The effect size due to triage method was 108 seconds/patient (95% CI 83-134 seconds/patient). The cumulative triage accuracy for the cCTAS and START tools were 70/90 (77.8%) and 65/90 (72.2%), respectively. The percent difference between cumulative triage was 6% (95% CI −19-8%). Conclusions: Triage nurses completed START triage 105 seconds/patient faster when compared to cCTAS triage and a similar level of accuracy between the two methods was achieved. However, when the typing time is taken into consideration cCTAS took 45 seconds/patient longer. The use of either CTAS or START in the ED during a MCI may be reasonable but choosing one method over another is not justified from this investigation. Résumé: Objectif: L'étude visait à comparer le temps de triage pris par le personnel infirmier de triage d'un service des urgences (SU) ainsi que la précision de la répartition des patients dans une simulation d'incident causant un très grand nombre de victimes corporelles à l'aide d'une version informatisée des méthodes ECTG ou START. Méthode: Il s'agit d'une étude pilote consistant en un essai prospectif mené sur un échantillon de commodité. En tout, 20 infirmières et infirmiers de triage au SU, répartis également en deux groupes de 10 sujets, ont participé à l'étude. Un questionnaire de papier présentait 9 simulations d'incident causant un très grand nombre de victimes corporelles. Après en être arrivé à un consensus sur la formulation des scénarios, un groupe d'experts s'est penché sur l'élaboration d'une échelle uniforme de triage permettant de comparer les participants entre eux. Enfin, le temps de triage et la précision du triage ont fait l'objet de comparaisons à l'aide, respectivement, d'une analyse de régression linéaire et d'un test du chi carré. Résultats: Le temps de triage moyen d'après les versions informatisées des méthodes ECTG (ECTGi) et START étaient de 138 s/patient et de 33 s/patient, respectivement. L'ampleur de l'effet liée à la méthode de triage était 108 s/patient (IC à 95 % : 83-134 s/patient). Pour ce qui est de la précision cumulée du triage, elle a atteint 70/90 (77, 8 %) et 65/90 (72, 2 %) pour les outils ECTGi et START, respectivement, ce qui donne un écart de 6 % (IC à 95 % : −19-8 %). Conclusions: Le triage effectué par le personnel infirmier selon la méthode START s'est réalisé 105 s/patient plus rapidement que selon la méthode ECTGi, et ce, pour un degré comparable de précision. Toutefois, la méthode ECTGi nécessitait 45 s/patient de plus si le temps de saisie des données était pris en considération. Il peut s'avérer judicieux de choisir la méthode ECTG ou la méthode START, au SU, durant un incident causant un très grand nombre de victimes corporelles, mais, d'après les résultats obtenus, rien ne justifie le choix d'une méthode plutôt que d'une autre.